2020
DOI: 10.1016/j.jhep.2020.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Precision medicine in variceal bleeding: Are we there yet?

Abstract: Variceal bleeding is one of the most feared complications of portal hypertension in patients with cirrhosis because of its deleterious impact on prognosis. Adequate management of patients at risk of developing variceal bleeding includes the prevention of the first episode of variceal bleeding and rebleeding, and is crucial in modifying prognosis. The presence of clinically significant portal hypertension is the main factor determining the risk of development of varices and other liver-related decompensations; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 111 publications
0
34
0
3
Order By: Relevance
“…Patients with acute VH who are more likely to fail, despite initial control of hemorrhage by standard therapy, are those belonging to Child C class or those with HVPG > 20 mmHg [50,55]. It was, therefore, postulated that the placement of a TIPS before failure of standard therapy ("pre-emptive TIPS") could improve survival [56]. A first RCT in which 52 patients with HVPG > 20 mmHg was randomized to standard treatment vs. pre-emptive TIPS (uncovered) demonstrated significantly lower failure rates and all cause short-term mortality in the TIPS arm (12% vs. 50% and 17% vs. 38%, respectively) [57].…”
Section: Preemptive Tips (In Patients At High-risk Of Failing Standard Therapy)mentioning
confidence: 99%
“…Patients with acute VH who are more likely to fail, despite initial control of hemorrhage by standard therapy, are those belonging to Child C class or those with HVPG > 20 mmHg [50,55]. It was, therefore, postulated that the placement of a TIPS before failure of standard therapy ("pre-emptive TIPS") could improve survival [56]. A first RCT in which 52 patients with HVPG > 20 mmHg was randomized to standard treatment vs. pre-emptive TIPS (uncovered) demonstrated significantly lower failure rates and all cause short-term mortality in the TIPS arm (12% vs. 50% and 17% vs. 38%, respectively) [57].…”
Section: Preemptive Tips (In Patients At High-risk Of Failing Standard Therapy)mentioning
confidence: 99%
“…Abundant research has shown that variceal bleeding and rebleeding are among the most serious complications of portal hypertension in patients with cirrhosis because of a severe impact on prognosis (11,56). Treating patients based on their individual risk of portal hypertension-related bleeding undoubtedly affects the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, EVL has been shown to result in lower rebleeding, mortality and complication rates compared with EIS (8)(9)(10). Transjugular intrahepatic portosystemic shunt (TIPS) is a metal stent that connects the hepatic vein and intrahepatic portal vein to effectively decrease portal pressure and prevent ascites aggravation and rebleeding (11). It is ideal to maintain the portal pressure gradient of the portal and inferior vena cava between 10 and 12 mm Hg (5).…”
Section: Introductionmentioning
confidence: 99%
“…Ressaltamos que a recorrência do sangramento em um ano pode ser de até de 60% e que a mortalidade atual de cada sangramento varia de 15-20%. Também chamamos atenção de que pacientes com varizes de médio/grosso calibre tem risco de sangramento de 25-30% em dois anos 4 .…”
Section: A R T I G Ounclassified